5-Fluorouracil-loaded chitosan nanoparticles conjugated with methotrexate for targeted therapy of colorectal cancer - dos Santos, Aline Martins [UNESP] (2025)
The poor prognosis of colorectal cancer (CRC) is mainly associated with the highly invasive nature, delayed diagnosis, multidrug-resistant cells, tumor recurrence, and metastasis. Targeted therapies offer a promising means to enhance drug accumulation at the tumor site with the aid of cell-targeting ligands. Herein, chitosan-based multifunctional nanoparticles, conjugated with methotrexate (MTX) by covalent bonds, were designed for targeted delivery of 5-fluorouracil (5-FU) to improve CRC therapy. The synthesis of MTX-conjugated CS was confirmed by Fourier transform infrared spectroscopy (FTIR) and Nuclear magnetic resonance spectroscopy (1H NMR) which showed the different degrees of CS-MTX conjugation (CS-MTX-1, CS-MTX-2 and CS-MTX-3), presenting a MTX content of 16.9, 27.5 and 30.8 %, respectively. MTX-conjugated nanoparticles containing 5-FU exhibited particle size ranged from 376.4 to 407.8 nm, high positive zeta potential and 5-FU encapsulation efficiency above 15 %. In vitro mucoadhesion assay demonstrated the mucoadhesive capacity of CS nanoparticles mainly at intestinal pH, and the conjugation of MTX to the nanoparticles reduced the mucoadhesiveness of the system, which in turn may interact specifically with tumor cells. Unconjugated and MTX-conjugated 5-FU loaded nanoparticles induced higher cytotoxic activity in HCT-116 cancer cells compared to free drugs at 24 h, with IC50 values below 27.44 μg/mL−1. Therefore, the developed systems are promising candidates as a targeted therapeutic approach for CRC treatment.